One-pot synthesis of acrylic acid from glycerol over SBA-15 supported heteropoly acid catalysts : Influence of mesoporosity and acidity - Muhammad Yusri, Ahmad; Syamima Nasrin, Mohamed Saleh; Ahmad Zuhairi, Abdullah (Elsevier B.V., 2024)
Heteropoly acids (HPAs) of the Keggin type exhibit substantial Brønsted acidity and are commonly utilized as acid catalysts, particularly in acrylic acid synthesis via glycerol oxydehydration. The primary goal of this research is to comprehensively assess the morphological and physicochemical properties of SBA-15 supported HPAs (H4SiW12O40.xH2O, H3PW12O40.xH2O, and H3PMo12O40.xH2O). The synthesized catalysts were characterized via physisorption analysis, XRD, SEM, FT-IR, NH3-TPD, and H2-TPR. Furthermore, the catalyst's catalytic activity in acrylic acid synthesis via single-step liquid phase glycerol oxydehydration was evaluated by correlating its characteristics with glycerol conversion and acrylic acid yields. The PW/SBA-15 catalyst exhibited the best performance, with the highest acrylic acid yield reaching 17.5 at 87.8 glycerol conversion. Given that the partial oxidation of acrolein to acrylic acid necessitates an optimal level of redox properties, the superior performance of PW/SBA-15 was characterized by high acid sites and moderate oxidative capabilities.